Nutrition-Sensitive Agricultural Interventions and Maternal and Child Nutrition Outcomes in Arid and Semi-Arid Lands of Kenya - Grant, F.; Amunga, D.; Kwikiriza, N.; Malit, J.; Moyo, M.; Mulwa, C.K.; Mwaura, L. (Elsevier, 2024)
Objectives: The objective of this study was to assess the effect of household participation in climate smart nutrition-sensitive agriculture (NSA) interventions on maternal and young child nutrition outcomes in Makueni, Garissa and Tana River counties. Methods: Data from a community-based cross-sectional survey conducted in Makueni, Garissa and Tana River counties was used. Caregivers’ knowledge of nutrition, health and childcare, women (MDD-W) and young child dietary diversity (MDD-C), vitamin A (VA) intakes, minimum meal frequency (MMF), and minimum acceptable diet (MAD) for children 6-23 months were analyzed. The comparison of means and proportions was assessed using Student’s t-test and the Chi-square test, respectively, between the caregivers participating in NSA interventions and non-participants. The impact of the level of participation in NSA interventions (nutrition training, use of infant feeding toolkit and access to orange-fleshed sweetpotato (OFSP) vines for cultivation) and information on how to utilize these to improve infant and maternal feeding in the household on caregiver knowledge and practices scores was examined using multiple regression. Results: Of 494 caregivers surveyed, 72% indicated to have participated in at least one study intervention. In adjusted analyses, participation in at least one of the study interventions was significantly associated with improved caregiver nutrition [β (SE): 0.943 (0.354), P< 0.001], and VA [0.613 (0.178), P< 0.001] knowledge scores and young child MMF [0.202 (0.069), P< 0.001] and MAD [0.111 (0.058), P< 0.10]. Independently, all three interventions (nutrition training, use of infant feeding toolkit and access to OFSP vines) significantly increased VA knowledge among caregivers (P 0.01) and infant MMF (P 0.05). Whilst the use of infant feeding toolkit and access to OFSP vines alone had a significant positive effect on MDD-W (P 0.01) and MDD-C (P 0.01). Conclusions: The findings show the need to integrate climate-smart NSA interventions in humanitarian settings to improve nutrition among women and young children. Such interventions can potentially enhance resilience among populations in these fragile environments to better withstand various shocks.